The Natural and Cultural Resources for Ecotourism Development in Trenggalek Regency, East Java - Zulia, Zulfaidha; Yanuwiadi, Bagyo (Journal of Indonesian Tourism and Development Studies, 2015)
Ecotourism is all of the activities that is responsible for maintaining the conservation and environmental education. This activities also involves the local communities to get some benefit. This research's aim are to determine some potentials objects and attractions for supporting ecotourism development program in Trenggalek Regency, East java. Field survey was conducted at Trenggalek Regency following several steps including preliminary study, field surveys, and interviews to several informants. Data obtained from interviews with several informants as well as from direct observations were analyzed by using descriptive analysis techniques. The results show that Trenggalek Regency have some potential resources for supporting ecotourism i.e. Geghog rice, Ayam Lodho, Alen-alen, Kripik Tempe, Tiban ceremony, Lowo Cave, Prigi Beach, Bamboo Handy Craft, Larung Sembonyo ceremony, Nyadran Ceremony, Clove plantation, and Cengkrong Beach. Each of those mentioned potential resources have different characteristics that can become supporting unit for ecotourism development. Keywords: community development, conservation, natural resources, sustainable tourism